A CULTURAL-BASED MEDIATION TO SOLVE DEFAMATION CASES: A FORENSIC LINGUISTIC STUDY - Inderasari, Elen; Kusno, Ali; Kusmanto, Hari (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
Defamation cases found through social media have increased significantly. The government has done restorative justice in handling defamation cases. This study aims to describe formulating a cultural-based mediation. This research is descriptive qualitative research. The data of this research was the language used on MY’s Facebook comment and police report regarding the case. An interactive model (data reduction, display, and conclusion drawing) is applied to analyze the data. The findings of this research show that cultural-based mediation may serve as an alternative to solving a defamation case as long as both parties share the same culture. It may be effective if the police have not yet handled the case and a third party who can act neutral and fair is present during mediation. If else, the case will be handled by the police, which can be based on an expert's opinion, the linguists.